Variations in single/two stage thyroidectomies for cancer may be due to differences in thyroid fine needle cytology provision. Issue 8 (August 2015) - Gandhi, A.; Ranganathan, B.; Thiryayi, S.A.; Rowland, M.; Yap, B.K.
Abstract Background & aims Recommended treatment for thyroid cancers >10 mm is single stage total thyroidectomy (SST). Cancers diagnosed by diagnostic lobectomy may need completion surgery resulting in two stage thyroidectomies (TST). We noticed significant variation in numbers of SST and TST between hospitals within our cancer network and explored reasons for this using a prospective database containing all cases from 2004 to 2011 (n = 1030). We therefore conducted a survey of thyroid cytology provision across the network during 2010–2011. Methods A central university hospital with the largest caseload (21.5% of total) was chosen as "benchmark". Of 14 remaining hospitals 3 were excluded from analysis due to low thyroid operation numbers and the remaining compared with benchmark. We used individual chi-squared tests with Bonferroni correction to explore variation in expected and observed numbers of SST/TST. Analysis of variance (ANOVA) was used to examine reasons for observed differences. Results Significant variance in SST/TST was seen between hospitals (p < 0.00001). Three hospitals had frequencies of SST statistically similar to reference hospital; each reported 201–300 thyroid cytology cases during the survey period. The remaining 8 had lower rates of SST, the 2 lowest performing hospitals having SST rates of 11% (p = 0.0004) and 9% (p < 0.0001). These eight hospitals reported fewer than 200 cytology cases each, shared amongst 4–7 pathologists per site. Differences were unrelated to patient age, gender, tumour histology or stage (ANOVA). Only the reference hospital had specialist cytopathologists. Conclusion Variation in thyroid cytology provision may increase TST rates. Thyroid cytology should be concentrated in high volume centres with specialist thyroid cytopathologists.